Influence of Substrate on Hafnium Silicate Metal-Insulator-Metal Capacitors Grown by Atomic Layer Deposition. (27th March 2015) - Hutchinson, B J; Teodorescu, V S; Negrea, R; Sheehan, B; Carolan, P; O'Brien, S; Modreanu, M; Pemble, M E; Povey, I. M
Abstract : In this paper we report on the structural and electrical properties of hafnium silicate films grown by atomic layer deposition on a platinum bottom electrode. The results are compared to previously published results from our laboratory for an aluminum bottom electrode structure, with otherwise identical processing of the dielectric layer. The results demonstrate that the bottom electrode has a marked effect on both the structure and electrical properties of the resulting MIM capacitor. The previously reported films on aluminum were found to exhibit excellent electrical properties over a range of substrate materials and were consistent with hafnium silicate. In this study high resolution transmission electron microscopy (HRTEM) analysis and Raman spectroscopy indicate that on platinum the main crystalline phase is monoclinic HfO2 with a dielectric constant ( k ) value of 18. Despite the crystalline nature of the HfO2 no hysteresis was observed in the capacitance voltage measurements. The scanning transmission electron microscopy (STEM) analysis also reveals the presence of nanoparticles, located primarily towards the lower platinum metal electrode at the HfO2 grain boundaries. Based on energy-dispersive x-ray spectroscopy (EDX) analysis the nanoparticles are consistent with silicon oxide inclusions.